DIVERSITY OF CRAB IN Mangrove Forest Ecosystems OF SELAT BARU BENGKALIS - Ahmad Saripuddin; Joko Samiaji; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in May-June 2015 in the mangrove forest ofSelat Baru ofBengkalis.The method used in this study was a survey method.Sampling was performed at the time of low tide. The location of sampling stations are divided into three observation stations. Station 1, located on mangrove areas adjacent to the shelter fish caught by fishermen, Station 2,was located in the mouth of theLiong rifer, station 3,was at the was mangrove forest area that was relatively still in good condition mangrove ecotourism area. Analysis of samples carried out in the Laboratory of Marine Biology, University of Riau.The study found 15 species of crab derived from 2 clases and 15 families.The results showed that the average density of crabs found in the station's highest density and lowest at station III II. Statistical analysis (ANOVA) note that abundance was not significantly different between stations on the level of confidence (F. 0.05).   Keywords: crab, Abundance, Organic Sediment, Selat Baru